Optionally Reinforced Columns Under Simulated Seismic and Time Varying Axial Loads: Advanced HYLSER-2 Testing - Ristic, Jelena; Guri, Zijadin; Ristic, Danilo (Civil Engineering Journal, 2024)
Steel- and composite-reinforced columns (SRC and CRC columns) provide alternative solutions for common and harsh environments. Although extensive research has been conducted on these columns, direct comparative studies of SRC and CRC columns under seismic conditions, with consistent testing and realistic load simulations, remain limited. This study examined the nonlinear seismic responses of nine ordinary steel-reinforced concrete column models constructed alternatively with normal-strength and high-strength concretes under simulated earthquakes and time-varying axial loads. A developed advanced HYLSER-2 seismic testing system was employed to conduct seismic tests. Spiral transversal reinforcement with pitches of 6.0 and 9.0 cm was used to explore the effects of concrete confinement. The HYLSER-2 seismic tests, conducted under various interactively simulated earthquake intensities and time-varying axial loads, yielded crucial experimental results. Additionally, an extensive complementary analytical study was conducted to provide comparative insights between steel-reinforced columns (SRC) and composite-reinforced columns (CRC) with novel glass fiber-reinforced (GFRP) bars. The analytical study was conducted using experimentally proven advanced nonlinear analytical micromodels. The analytical results highlight the hysteretic behavior of columns reinforced with ordinary steel and novel GFRP reinforcing bars under the simulated combined effects of reversed cyclic bending and time-varying axial loads. The findings form a critical basis for advancing seismic design strategies for SRC and CRC columns exposed to strong earthquakes and high-time variations in axial loads. Doi: 10.28991/CEJ-2024-010-10-09 Full Text: PDF